Impact of laser energy density on the structure and properties of laser-deposited Fe‒Ni‒Ti composite coatings - Wang, Zhen; Zhang, Jian; Zhang, Fengqin; Qi, Changbao (Frontiers in Materials, 2024)
To utilise laser deposition for the preparation of high-strength, wear-resistant components, the service life of components in rail transportation equipment should be improved. Laser deposition technology is used to fabricate Fe-Ni-Ti coatings on the surface of AISI 1045 steel substrates. By varying the laser power to adjust the laser energy density, Fe-Ni-Ti composite coatings are prepared at various energy densities. The morphology, microstructure, phase composition, tensile strength, microhardness, and friction-wear characteristics of the composite coatings are observed and tested.The influence patterns and mechanisms of laser energy density on the organisational variation and friction-wear performance of composite coatings is investigated. When the laser energy density is 97.2 J/mm² (1400 W), the residual stresses in the deposition layer are minimised, resulting in fewer cracks and gas pore defects, with a porosity rate reaching its lowest value of 1.2% and a density of 99.1%. With the increase in energy density, both the tensile strength and elongation of the deposited layer exhibited an initial increase followed by a decrease. The hardness and wear resistance of Fe-Ni-Ti deposition layers is effectively controlled by regulating the laser energy density.